Sistemas tradicionales de gestión del bosque tropical en Indonesia: ecología y prácticas silviculturales - García Fernandez, C. (Universidad Complutense de Madrid, 2001)
Tropical forests have been perceived as biodiversity sanctuaries that should be preserved from human action. However, rural communities have lived in these forests over millennia using their biodiversity to satisfy a wide range of needs (timber, food, medicinal plants, etc.), without threatening the long run benefits they provide. Non-Timber Forest Products (NTFPs) were identified as a valid option to achieve sustainable development. Recently, traditional forest management systems, created and implemented by rural communities, have been identified as another way to favor the sustainable use of these areas. Management practices are extremely complex and ever changing to fit the different environmental, cultural and economic conditions of each territory. The study conducted is focused in two traditional management systems in Indonesian forest, third country in extension of tropical forest after Brazil and Zaire. The resources studied, exploited in small management units (gardens), are benzoin resin (Styrax paralelloneurum) and rattan canes (Calamus caesius). Both are forest resources classified as NTFPs. Benzoin is a tree characteristic of mature forest that requires shade in the first stages of growth, therefore it is planted under forest cover once the undergrowth vegetation have been eliminated. After the first years the samplings need more sunlight so it become independent of the forest that provided shelter. Therefore regular clearance is practiced once the exploitation of the resin starts, seven to ten years after the planting. On the other hand, rattan is a multi stemmed climbing palm that it is established together with rice in shifting cultivation plots where all the vegetation have been eliminated. After one or two years the plot is abandoned and the rattan grows with the secondary vegetation. This palm will need trees to climb to so the canes have good quality. In this systems the silvicultural activities are directed to maintain a forest cover that it is not too dense, it would not allow sunlight to come in, not too open, which would restrict climbing possibilities. Silvicultural practices are human alterations of the natural dynamics of forest and therefore they can provoke structural changes in forest structure. Benzoin gardens the density of Styrax trees is the main discriminant variable. They can go from the plantation extreme (where 80% of the trees above 10 cm dbh are cultivated) to the forest like extreme (benzoin represents 45% of the stems), with presence of lianas, epiphytes and other elements of mature forest. In the first case, even with high density of plantation (477 tress/ha) the undergrowth vegetation is clear but diverse, which differentiate them from real plantations, that are monospecific, and that require in general external inputs. Rattan gardens on the other extreme are structurally more similar to a forest. Tree density (dbh³ 10 cm) ranges from 374 to 651 compare to 600 trees/ha in primary forest areas. Differences are related tree cover and size and with Calamus clusters density. This uniformity is an indication of the low intensity of management required to keep the gardens in good conditions. A parameter with major importance in the context of this work is the diversity this gardens hold compared to the one in mature forest areas.